2018
DOI: 10.1016/j.bja.2018.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Fascial layers influence the spread of injectate during ultrasound-guided infraclavicular brachial plexus block: a cadaver study

Abstract: When fascial layers are present in the neurovascular sheath, they impede the spread of injectate during infraclavicular brachial plexus block. Ultrasound detection of these fascial layers is unreliable in cadavers. These findings support the use of greater volumes of injectate or a multiple injection technique when performing this block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
3
17
0
2
Order By: Relevance
“…In support of previous studies (Brenner et al, 2018; Layera et al, 2020; Monzó & Hadzic, 2020; Morimoto, Popovic, Kim, Kiamzon, & Rosenberg, 2007), we also demonstrated a barrier that presented as a septum between two well‐defined groups of clusters: the lateral cord superficially, and the medial and posterior cords more posteriorly (deeper). The LA was clearly confined to the compartment into which it was injected, supporting the findings of Morimoto et al (2007) and Brenner et al (2018). This would clearly result in variable blockade results if single injections were performed, and also, in principle, in secondary blockade failure for continuous blocks in which the catheter is not placed in the correct or desired compartment(s).…”
Section: Discussionsupporting
confidence: 91%
“…In support of previous studies (Brenner et al, 2018; Layera et al, 2020; Monzó & Hadzic, 2020; Morimoto, Popovic, Kim, Kiamzon, & Rosenberg, 2007), we also demonstrated a barrier that presented as a septum between two well‐defined groups of clusters: the lateral cord superficially, and the medial and posterior cords more posteriorly (deeper). The LA was clearly confined to the compartment into which it was injected, supporting the findings of Morimoto et al (2007) and Brenner et al (2018). This would clearly result in variable blockade results if single injections were performed, and also, in principle, in secondary blockade failure for continuous blocks in which the catheter is not placed in the correct or desired compartment(s).…”
Section: Discussionsupporting
confidence: 91%
“…The differences among studies may be due to differences in the details of the injection techniques, such as the injection duration and pressure limit, as well as differences in the definition of successful blockade [10,19,22]. Several studies have identified the fascial layer within the neurovascular sheath of the brachial plexus [34,35] as a layer that may impede the spread of local anesthetic. In contrast to the single injection technique utilized in the dose-finding study for the CCB [10], the present study used a two-injection technique.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Morimoto and colleagues reported the existence of the posterolateral septa to the axillary artery in 15% of ICBPS in patients 5. In a more recent cadaveric study, a lower septum was identified in 60% of dissections that received an injection at the level of ICBPS 6…”
mentioning
confidence: 99%